Peran Ikatan Remaja Masjid Jami’atul Khoir dalam Memberikan Pemahaman Nilai-Nilai Pendidikan Islam Pada Remaja di Desa Namang - Armika Armika (JYRS: Jurnal Online Mahasiswa Program Studi Fakultas Syariah dan Ekonomi Islam, 2022)
IRMAS (Masjid Youth Association) Jami'atul Khoir is a Muslim youth organization that plays an important role in the prosperity of mosques and provides an understanding of the values ​​of Islamic education for youth. In adolescence, they feel that they are not children anymore but they also have not been able to take responsibility as adults do in which it creates an instability in adolescents that can be seen from their daily behavior at home, at school, and in the community. Therefore, it was necessary to instill the values ​​of Islamic education in a teenager, with the aim that the teenagers had good morals, and made them fully human. The author's purpose of raising this issue was to reveal the role of IRMAS and its activities in providing an understanding of the values ​​of Islamic education for adolescents in Desa Namang, as well as knowing the conditions of implementation of Islamic education values ​​on adolescents in Desa Namang. The activities done by IRMAS Jami'atul Khoir were expected to fortify teenagers’ lives with Islamic atmosphere. This was a qualitative research providing reports of research results by describing and explaining the data obtained from interviews, observations and documentation. The results of this study were: 1. The roles of IRMAS in providing Islamic educational values ​​for adolescents in Desa Namang were as the actualization of education, instilling the attitude of Ukhwah Islamiyah, minimizing juvenile delinquency, 2. The activities that were done in IRMAS Jami'atul Khoir of Desa Namang in an effort to provide an understanding of the values ​​of Islamic education to teenagers namely conducting religious studies, holding PHBI (Islamic Holidays Commemoration) events, holding joint yasinan, running small businesses and holding joint discussion activities.